Returning to Education After the Earthquake in the Perspective of Teachers in Provinces Declared as Disaster Areas: Problems and Solution Suggestions - Fatih Özdemir; Mustafa Erol (Sakarya University, 2024)
This research aims to reveal the problems experienced in returning to education after the earthquake in the provinces declared disaster areas and the solutions for the problems. For this purpose, the research was carried out within the scope of phenomenology, one of the qualitative research designs. The research group consisted of nine teachers working in Kahramanmaraş, Gaziantep, Hatay, Malatya and Adıyaman provinces of Türkiye. The sample of the research was determined according to the maximum diversity of purposeful sampling types. Data in the research were collected online with a semi-structured interview protocol. Content analysis technique was used in the analysis of the obtained data. The research findings are grouped under three themes: problems experienced, solutions produced, and suggestions. While the problems experienced by the teachers were examined under the titles of not being able to meet basic needs and being anxious, the problems experienced by the students were examined under the titles of transportation and absenteeism. The solutions produced were examined under the headings of establishing one-to-one communication with students, organizing activities for harmony and bonding, and providing academic support to ensure equality of opportunity.